Stability analysis and controller parameter optimization method for ship power electronic propulsion system based on Middlebrook criterion - Chenghu XU; Weibo LI; Hao ZHANG; Zhiming PENG; Hualiang FANG (Zhongguo Jianchuan Yanjiu)
Objective Aiming at the stability problem of naval DC propulsion systems with a significant proportion of power electronic devices, a stability analysis and controller parameter optimization method based on the Middlebrook impedance ratio stability criterion is proposed.MethodFirst, the small-signal output impedance of the DC bus and small-signal input impedance of the inverter and motor are deduced and established through the simplification of the system model, linearization of the nonlinear system, dq transformation of the three-phase AC system, etc. The controller parameters are then optimized using a particle swarm algorithm to minimize the value of support capacitance on the condition of ensuring system stability. Finally, a simulation model of the DC propulsion system is constructed to simulate and analyze the influence of the support capacitance and equivalent resistance and inductance of the DC bus on the stability of the system.ResultsThe simulation results show that the system's stability margin is obviously improved after the controller parameters are optimized by the particle swarm algorithm, which in turn lowers the value of support capacitance and reduces the overall size of the DC propulsion system's converter.ConclusionThe findings of this study can provide useful references for research on voltage oscillations and their suppression in integr-ated power systems with a significant proportion of power electronic devices.